PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN HASIL BELAJAR MENGGAMBAR BUSANA DI SMK NEGERI 8 MEDAN - Rambe, Armaini; Anggraini, Yudhistira (TABULARASA, 2014)
The purpose of this research is to improve student learning outcomes in subjects with a fashion drawing using Model-Based Learning Portfolio. The research was conducted in SMK Negeri 8 Medan. This research is a class act that is carried out in two cycles. Subjects in this study were students of class XI Clothing 2 amounted to 36 people. Data was collected through tests, observations and questionnaires. Data was analyzed using descriptive analysis. The results of the analysis of the data obtained pre-test as early learning outcomes of students with 38.89% were completed with an average value of 56.79. Data post-test cycle I with an average value of 64.51 with 50% of students who meet the completeness. Meanwhile, the data post-test cycle II with an average value of student learning outcomes 78.81 with 83.33% of students who achieve a minimum completeness criteria (KKM). The data indicate that there is an increase in student learning outcomes of the post-test, the first cycle to post-test cycle II of 33.33%. Observations have shown an increase in the activity of students by 25%. (Cycle I 2,77,% 27.77% whereas the second cycle) with excellent assessment criteria.